Metodologías ágiles: un análisis de los desafíos organizacionales para su implementación - Flores-Cerna, Fernando; Sanhueza-Salazar, Víctor-Manuel; Valdés-González, Héctor-Moisés; Reyes-Bozo, Lorenzo (Revista Científica, 2021)
The objective of this research is to determine the main existing gaps before implementing agile methodologies in IT-SMEs (Information Technology - Small and Medium-Sized Enterprises) with traditional methodology for project management. To this effect, a qualitative approach to the opinions of three managers, two project engineers, and six programmer analysts of a company is proposed, which is based on semi-structured interviews, considering a convenience sample, in order to understand the existing difficulties in the company under study, contrasting this reality through surveys aimed at 29 IT professionals from other organizations. The results of the analysis reveal that the main gaps for the implementation of agile methodologies in SMEs are organizational culture at odds with agility, lack of commitment from management, and resistance to change. It is concluded that the proposal turns out to be effective for understanding the main gaps to be solved before starting the implementation of an agile methodology in an IT-SME, thus allowing the organization to be aligned with agility.